FACTORS INFLUENCING LOW SCIENCE LITERACY AND SCIENCE LEARNING OUTCOMES OF GRADE VIII STUDENTS OF SMP NEGERI 1 AEK KUO: AN ANALYSIS - Asri Azrani; Novi Fitriandika Sari; Ika Chastanti (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study analyzes the factors that influence the low scientific literacy and science learning outcomes of eighth-grade students of SMP Negeri 1 Aek Kuo. The scientific literacy skills of students in Indonesia are still very low based on PISA data, with Indonesia's average score always at the bottom. This study uses a quantitative descriptive method with a total sampling technique, involving 141 students from grades VIII-1 to VIII-5 of SMP Negeri 1 Aek Kuo. Data were collected through a questionnaire with 25 Likert-scale statements and analyzed using a percentage formula for each indicator. The results of the study identified five main factors that influence the low scientific literacy and science learning outcomes: misconceptions 77.29% (high), non-contextual learning 75.05% (moderate), selection of textbooks 62.23% (moderate), low reading ability 48.08% (low), learning environment and climate 45.08% (low). This study concludes that misconceptions and non-contextual learning are the main challenges that contribute to factors influencing low scientific literacy and science learning outcomes.